Ikan Green Severum Heros appendiculatus: Teknik Pembenihan Untuk Meningkatkan Produksi Benih Ikan Hias Air Tawar - Iskandar, Andri; Hendriana, Andri; Endrassanto, Nabilla Putri; Febriana, Muyke; Denmar, Kemas; Wahyudi, Imam Tri; Kurniawinata, Mohamad Iqbal; Rafiuddin, Muhammad Ahya (Universitas Batangahari Jambi, 2026)
The Green Severum Heros appendiculatus is a species of freshwater ornamental fish originating from the northern United States. Currently, its aquaculture industry is expanding due to its high economic value, which is expected to contribute to community welfare by creating job opportunities and increasing export value. This study aims to disseminate technical information on Green Severum breeding, as limited data is available on its cultivation management. Technically, this fish can be used as broodstock at 10–14 months of age, with a sex ratio of 1 male to 1 female. During the breeding period, broodstock is fed natural feed, including Tubifex sp. (silk worms) and Lumbricus sp. (earthworms). The spawning process occurs naturally using PVC pipes as spawning substrates. The study results indicate that the average fertilization rate (FR) is 90%, the hatching rate (HR) is 95%, and the survival rate (SR) is 93%.